If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(m + -3) = 4 Reorder the terms: 2(-3 + m) = 4 (-3 * 2 + m * 2) = 4 (-6 + 2m) = 4 Solving -6 + 2m = 4 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2m = 4 + 6 Combine like terms: -6 + 6 = 0 0 + 2m = 4 + 6 2m = 4 + 6 Combine like terms: 4 + 6 = 10 2m = 10 Divide each side by '2'. m = 5 Simplifying m = 5
| -1.2+3.618= | | 86+2(3x-12)=180 | | 1-2y+2=0 | | 120x-(5000-0.75x)= | | (x-1)(x-3)(x-5)(x-7)=20 | | (X-8)33=180 | | 8+n*2n=72 | | 5.4-0.103= | | 2k=p+2v | | 4x=18.8 | | 12*x=-3 | | 6x+3500=4x+4000 | | 86+2(3x-12)= | | 3(2x+1)x=-39 | | 8.3-(-2.1)= | | 5=q+12 | | 9x^3+6x^3+7= | | 120(5000-0.75x)= | | y=-16t^2+64t+8 | | .02y+.18=3 | | 0+4+4x= | | (3x-20)+(2x)=180 | | 6-9-d=3d | | 7.3+1.9y-(4.7x+5.8y)= | | Y=7*4x | | 1/2x+x= | | 0.21x-55=29 | | q^2-12q+20=0 | | -1x-5x=12 | | 2(3x+1)=15 | | 4m+6n-8+(8m-3)= | | -19=x-11 |